PENGARUH DEFERENSIASI PRODUK PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION PADA UD. SINAR MULIA DI KABUPATEN GIANYAR - Sumerta, I Komang; Indahyani, Desak Nyoman Tri; Redianingsih, Ni Komang; Pranawa, I Made Baji (Buletin Studi Ekonomi; VOL.25.NO.2.AGUSTUS 2020, 2020)
Consumer purchasing decisions is the occurrence of sales fluctuations in the past four years. Product differentiation, promotion, and price are factors that have been pursued by the company but have not been able to provide a maximum contribution to consumer decisions. The purpose of this study was to determine the effect of product differentiation, promotion, and price on fashion product purchasing decisions. The sample was determined by purposive random sampling technique, with 105 respondents. The data collection technique used was a questionnaire (questionnaire). The analysis technique used the SPSS version 22. The results showed there was an effect of product differentiation, promotion, and price simultaneously on the decision to purchase fashion products. Based on the partial test results it can be seen that product differentiation, promotions, and prices have a positive and significant effect on purchasing decisions for fashion products. The conclusion from this research is the higher product differentiation, promotion, and price, the decision to buy products fashion will increase. Suggestions for further researchers is to be able to conduct research on different subjects and by developing other independent variables.